Summary of PRSC Installations Addressed in the Integrated Natural Resources Management Plan and Natural Resources Considerations - 611th Civil Engineer Squadron (2020)
A summary table from the Pacific Regional Support Center installations that were addressed in the 2020 Integrated Natural Resources Management Plan and Natural Resources Considerations.